EFFORTS TO PRESERVE BATAK CULTURE THROUGH LOCAL WISDOM CORNER SERVICES AT THE UNIVERSITY OF NORTH SUMATRA LIBRARY - Rustika Nababan; Fransiska Timoria Samosir; Rahmat Alifin Valentino (JIPI (Jurnal Ilmu Perpustakaan dan Informasi), 2026)
This study aims to analyze the role of local wisdom corner services in preserving Batak culture at the University of North Sumatra (USU) Library. The research method used is qualitative with a case study approach through interviews, observations, documentation and literature review. The results of the study indicate that cultural preservation is carried out through collection management, distribution, physical preservation of library materials of Batak cultural collections and even efforts to digitize the collection. The process of preserving Batak cultural knowledge is carried out through six stages, namely identification, validation, documentation, storage, transfer, and dissemination. The preserved cultural collections reflect the cultural dimensions according to Hofstede, which include symbols, figures, rituals, and values. However, there are several obstacles that cause this service to be less than optimal, such as limited collections, lack of collaboration, the absence of SOPs and the lack of cultural programs or promotions. This study confirms that local wisdom corner services can be a model for university library-based cultural preservation that not only functions as a collection provider, but also as a manager and disseminator of indigenous knowledge. Therefore, policy support, collaboration with cultural institutions, and sustainable service development are needed so that cultural preservation can run more optimally.